2021
DOI: 10.7150/ijms.51842
|View full text |Cite
|
Sign up to set email alerts
|

Great Expectations: Induced pluripotent stem cell technologies in neurodevelopmental impairments

Abstract: Somatic cells such as skin fibroblasts, umbilical cord blood, peripheral blood, urinary epithelial cells, etc., are transformed into induced pluripotent stem cells (iPSCs) by reprogramming technology, a milestone in the stem-cell research field. IPSCs are similar to embryonic stem cells (ESCs), exhibiting the potential to differentiate into various somatic cells. Still, the former avoid problems of immune rejection and medical ethics in the study of ESCs and clinical trials. Neurodevelopmental disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 161 publications
(214 reference statements)
0
3
0
Order By: Relevance
“…To ensure that no chromosomal aberrations occurred in the reprogramming of newly generated iPSCs, we performed karyotyping of selected clones before downstream characterization [ 34 , 35 ]. Using conventional cytogenetics, a normal karyotype was ascertained in the iPSCs, which presented 22 pairs of autosomes and two sex chromosomes (XX) ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…To ensure that no chromosomal aberrations occurred in the reprogramming of newly generated iPSCs, we performed karyotyping of selected clones before downstream characterization [ 34 , 35 ]. Using conventional cytogenetics, a normal karyotype was ascertained in the iPSCs, which presented 22 pairs of autosomes and two sex chromosomes (XX) ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…The studies of epigenetics, neuroimmunology, and neurobiology in ASD indicated that cell therapy was an effective approach for treating the core symptoms of ASD ( Vaccarino et al, 2011 ; Siniscalco et al, 2012b ; Liu et al, 2019 ; Zhang et al, 2021 ). Two outstanding features of stem cells are the intense immunosuppressive activity that allows them to be used in autologous or heterologous transplantation ( Siniscalco et al, 2012a ) and paracrine actions ( Baraniak and McDevitt, 2010 ; Siniscalco, 2012 ).…”
Section: Treatment and Intervention Of Repetitive Restricted Behaviorsmentioning
confidence: 99%
“…First, the neurobiological functions of TAO kinases should be further investigated. At the molecular level, identification of specific up- and down-stream substrates for TAO kinases in different model systems, especially by combining human induced pluripotent stem cell (iPSC) from patients, is crucial for a better understanding of the mechanisms leading to the onset of a disease-phenotype (Parenti et al, 2020 ; Zhang et al, 2020 ). At cellular level, previous reports focus on the cell-autonomous role of TAO kinases in regulating the development of dendrites and dendritic spines.…”
Section: Conclusion and Perspectivementioning
confidence: 99%